Clinical efficacy of intra-articular infusion of cocktail combined with tranexamic acid in the treatment of middle-age and older patients with frozen shoulder following arthroscopic capsular release - Bai, Xiaojin; Bai, Fan; Wang, Zhi; Zhang, Yan; Liu, Fuying; Wang, Qibing (Frontiers in Surgery, 2023)
Objective To investigate the clinical efficacy of arthroscopic capsular release and postoperative intra-articular infusion of cocktail combined with tranexamic acid (TXA) in the treatment of patients with frozen shoulder. Method A total of 85 middle-aged and older patients with frozen shoulder who underwent arthroscopic capsular release and received intra-articular infusion of TXA alone (n = 28), cocktail alone (n = 26), and cocktail plus TXA (n = 31) after surgery were retrospective analyzed. The drainage volume within 24 h after surgery, postoperative length of hospital stay, postoperative complications, visual analog scale (VAS), Neer shoulder assessment scale, ASES score, and range of motion (ROM) of the shoulder joint at 1 day, 1 week, 1 month, and 3 months after surgery in all three groups were recorded and compared. Results Postoperative length of hospital stay was significantly shorter in the cocktail + TXA and cocktail groups than that in the TXA group. Postoperative drainage volume was significantly higher in the cocktail group compared with TXA + cocktail group (P < 0.05). At 1 day and 1 week after surgery, pain was more pronounced in the TXA group, which was significantly relieved in the cocktail and the cocktail + TXA groups (P < 0.05). Pain was significantly relieved in all the three groups at 1 and 3 months after surgery. Significant functional improvement of the shoulder was achieved in all three groups at 1 week after surgery, the improvement was apparent in the cocktail + TXA groups (P < 0.05), followed by the cocktail group. At 1 month after surgery, patients in the cocktail + TXA groups obtained excellent functional recovery of the shoulder joint. At 3 months after surgery, patients in all the three groups both obtained good recovery of the shoulder joint function, and the recovery was apparent in the cocktail + TXA groups (P < 0.05). Conclusion Arthroscopic capsular release and postoperative intra-articular infusion of cocktail combined with TXA has good safety and efficacy in the treatment of middle-age and older patients with frozen shoulder, which can reduce postoperative pain and intra-articular bleeding, promote early postoperative functional exercises and accelerate early postoperative recovery.